Foundations of software science and computation structures : 22nd International Conference, FOSSACS 2019, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2019, Prague, Czech Republic, April 6-11, 2019, Proceedings /: 22nd International Conference, FOSSACS 2019, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2019, Prague, Czech Republic, April 6-11, 2019, Proceedings. (2019) - Unknown
No abstract available